EVALUATING THE EFFECTS OF OXIDANTS ON CANOLA GROWTH AND YIELD AT URBAN, RURAL ROADSIDE AND RURAL REMOTE SITES USING ETHYLENEDIUREA IN LAHORE-PAKISTAN - S. Ahmed (Journal of Animal and Plant Sciences, 2015)
Canola (Brassica napus L.) plants were grown using and without using the ozone protectant ethylenediurea at rural, remote rural and urban roadside in and nearby the city of Lahore, Pakistan. The yield and growth of canola was assessed in 2 successive canola growth seasons. NO and photochemical oxidants concentrations were measured at rural, remote 2 rural and urban sites along roadside. Greater increases in yield and its components in both canola cultivars were recorded in EDU-SD treatment plants when compared to their NEDU counterparts. However, the differences between EDU-SD and EDU-FS treatments were much small compared with those between EDU-SD and NEDU. The effect on yield of EDU-SD at the urban site (BG) (64% & 48% increase in per plant seed weight for cv. Dunkeld and Cyclon respectively for the second growth season relative to the untreated plants (NEDU). ozone concentration, then this would point out the
Keywords: Canola; Growth; Ozone; Yield; Lahore; Pakistan.